2013
DOI: 10.3959/1536-1098-69.2.81
|View full text |Cite
|
Sign up to set email alerts
|

Signal Strength In Sub-Annual Tree-Ring Chronologies fromPinus ponderosaIn Northern New Mexico

Abstract: The creation of chronologies from intra-annual features in tree rings is increasingly utilized in dendrochronology to create season-specific climate histories, among other applications. A conifer latewood-width network has recently been developed for the southwestern United States, but considerable uncertainty remains in understanding site and species differences in signal strength and sample depth requirements. As part of the 22nd annual North American Dendroecological Fieldweek, the first Pinus ponderosa ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The pairwise correlation between EW and LW was tested. EW has a strong relationship with LW in our study, which supports the findings from another study in the southwestern United States [65]. This conclusion is also consistent with those for other tree species royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Discussionsupporting
confidence: 93%
“…The pairwise correlation between EW and LW was tested. EW has a strong relationship with LW in our study, which supports the findings from another study in the southwestern United States [65]. This conclusion is also consistent with those for other tree species royalsocietypublishing.org/journal/rsos R. Soc.…”
Section: Discussionsupporting
confidence: 93%
“…Multi-century and even multi-millennial tree-ring chronologies detail the seasonal and annual climate variability experienced by temperate, boreal, and alpine trees over the course of their lifespan (Mann et al 1998;Cook et al 2004;Griffin et al 2011;Williams et al 2012;Belmecheri et al 2015). For example, winter precipitation and summer temperature are the most influential growth factors for trees in semi-arid regions (Touchan et al 2011;Brice et al 2013; St. George and Ault 2014; St. George 2014) whereas forests in more mesic environments are most strongly influenced by summer precipitation (St. George et al 2010;St. George 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Out of nine investigated BI parameters, peak height, width, and area showed the strongest common signal among trees as expressed by the Rbar. This common signal was weaker than those observed in EWW and TRW-which are characteristically high at sites from the US Southwest (Brice et al 2013)-but comparable to that found in LWW adj . As the latter parameter has been used for dendroclimatological purposes in this region (e.g.…”
Section: Discussion and Conclusion A Novel Application Of The Blue In...mentioning
confidence: 43%